2014
DOI: 10.1186/1471-2407-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl-4-hydroxylase α subunit 2 promotes breast cancer progression and metastasis by regulating collagen deposition

Abstract: BackgroundIncreased collagen deposition provides physical and biochemical signals to support tumor growth and invasion during breast cancer development. Therefore, inhibition of collagen synthesis and deposition has been considered a strategy to suppress breast cancer progression. Collagen prolyl-4-hydroxylase α subunit 2 (P4HA2), an enzyme hydroxylating proline residues in -X-Pro-Gly- sequences, is a potential therapeutic target for the disorders associated with increased collagen deposition. However, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
398
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 530 publications
(434 citation statements)
references
References 55 publications
27
398
4
1
Order By: Relevance
“…We also found five of these proteins exclusively with TRIzol© extraction and seven exclusively using Laemmli extraction (Supplemental File #1). Comparisons with the EV proteins identified by Kruger [25] from MDA-MB-231 EVs showed that we identified 28 of 88 reported proteins (Supplemental File#1). From the top 25 proteins listed in Exocarta, 16 proteins were identified using both extraction methods, while a single hit was exclusive to Laemmli extraction (Table 1).…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…We also found five of these proteins exclusively with TRIzol© extraction and seven exclusively using Laemmli extraction (Supplemental File #1). Comparisons with the EV proteins identified by Kruger [25] from MDA-MB-231 EVs showed that we identified 28 of 88 reported proteins (Supplemental File#1). From the top 25 proteins listed in Exocarta, 16 proteins were identified using both extraction methods, while a single hit was exclusive to Laemmli extraction (Table 1).…”
Section: Resultsmentioning
confidence: 81%
“…Three publications have reported specifically on proteins identified in MCF-7 EVs [2325]. Additionally, based on the results from 59 cancer cell lines, Hurwitz [23] compiled a list of 213 proteins with unique gene symbols found to be common to multiple cancer cell lines, including MCF-7.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations